2020
DOI: 10.1111/ajco.13482
|View full text |Cite
|
Sign up to set email alerts
|

Changes in DNA methylation after 6‐week exercise training in colorectal cancer survivors: A preliminary study

Abstract: Aim: Behavioral interventions such as exercise may induce epigenetic changes. Only few studies investigated the effects of exercise on epigenetic alterations in colorectal cancer survivors. The aim of this study was to explore the changes of genome-wide DNA methylation after 6-week exercise training in colorectal cancer survivors. Methods: This preliminary study used a subset of data from a randomized controlled trial in 15 colorectal cancer survivors. Participants were randomized either to the 6-week exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“… 45 , 55 Many factors can influence the methylome of cancer survivors over time; one example being patients placed on exercise regimens having different DNAm patterns and epigenetic aging compared those that do not. 86 , 87 , 88 What might be more practical in selecting measurement timing, given unknown potential variability of DNAm over time, is to select measurement time points specific to when clinical outcomes are expected to occur. Having longitudinal studies with DNAm measurements prior to therapy initiation and follow up measurements timed with relevant clinical assessments is an ideal approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 45 , 55 Many factors can influence the methylome of cancer survivors over time; one example being patients placed on exercise regimens having different DNAm patterns and epigenetic aging compared those that do not. 86 , 87 , 88 What might be more practical in selecting measurement timing, given unknown potential variability of DNAm over time, is to select measurement time points specific to when clinical outcomes are expected to occur. Having longitudinal studies with DNAm measurements prior to therapy initiation and follow up measurements timed with relevant clinical assessments is an ideal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, multiple studies also showed persistent changes over multiple years, or significant differences between cancer survivors and matched healthy controls many years removed from their active therapy 45,55 . Many factors can influence the methylome of cancer survivors over time; one example being patients placed on exercise regimens having different DNAm patterns and epigenetic aging compared those that do not 86–88 . What might be more practical in selecting measurement timing, given unknown potential variability of DNAm over time, is to select measurement time points specific to when clinical outcomes are expected to occur.…”
Section: Discussionmentioning
confidence: 99%
“…While the mechanisms through which physical activity influences health and survival outcomes remain poorly understood, emerging findings from epigenetic studies, including a recent study published in the Asia Pacific Journal of Clinical Oncology involving colorectal cancer patients, suggest that physical activity may influence gene expression 1 .…”
Section: Is Exercise Really Safe Feasible and Effective For All People Diagnosed With Cancer?mentioning
confidence: 99%